GaAs OPFET characterisation considering concentration dependent carrier mobility and life time - Mitra H.; Lohani R.B.; Shubha; Khan R.U.; Pal B.B. (My University, 2025)
Mobility and life time of carriers are strong functions of impurity concentration. In GaAs OPFET characterization we assume these parameters as a function of impurity concentration in the channel and obtained closed form solution for the I-V characteristics and transconductance of the device. The results indicate that the concentration dependent mobility and lifetime have strong effect on OPFET characteristics. The results have been compared with experimental data and exhibits good agreement. © 1999 Taylor & Francis Group, LLC.